2012
DOI: 10.1002/sca.21039
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐Computed Tomography and Scanning Electron Microscopy Comparisons of Two Nickel–Titanium Rotary Root Canal Instruments Used With Reciprocating Motion

Abstract: The single-file root canal instrumentation technique using reciprocating motion has been gaining concern. Therefore, the purpose of this study was to compare the shaping ability of single ProTaper F2 file and WaveOne Primary file when they were used in the curved root canal with reciprocation motion and to investigate the durability of the file after use with a scanning electron microscopy (SEM). Changes in structure model index (SMI), root canal volume, curvature, surface area, and degree of transportation we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
1
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 28 publications
3
32
1
9
Order By: Relevance
“…For all assessed variables, comparison data are available (eg, the reported amount of removed dentin volume varied from 0.5 to 3.5 mm 3 [15,16], with the majority of the studies showing values in the range of 1-2.5 mm 3 [17][18][19][20][21][22][23]). These sizable differences may be explained by differences in initial canal anatomy and selecting the volume of interest as much as the preparation technique itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For all assessed variables, comparison data are available (eg, the reported amount of removed dentin volume varied from 0.5 to 3.5 mm 3 [15,16], with the majority of the studies showing values in the range of 1-2.5 mm 3 [17][18][19][20][21][22][23]). These sizable differences may be explained by differences in initial canal anatomy and selecting the volume of interest as much as the preparation technique itself.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that severe canal transportation (eg, strip perforation) is related to inferior outcomes (3); hence, numeric comparison of canal transportation is frequently done in the assessment of preparation quality. A variety of methods have been used in mCT-based studies (20,23,(29)(30)(31) (eg, vector-based and trigonometry-based numbers). Because these assessments provide partial scores, including the direction of transportation, it is again difficult to directly compare the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The WaveOne (WO, Dentsply Tulsa Dental) is a reciprocating system that includes 3 instruments with an apical concave triangular cross-section and reverse cutting blades (14). These instruments were specifically designed to minimize the risk of instrument fracture and oscillate at approximately 350 rpm with 30 clockwise and 150 counterclockwise rotation angles (15). It seems that reciprocating systems tend to push more debris and irrigants toward the periapical tissues than rotary systems (16).…”
mentioning
confidence: 99%
“…Due to the fact that the counterclockwise angle is greater than the clockwise one, it is claimed that the instrument continuously progresses toward the terminus of the root canal. Both instruments have been evaluated in preliminary studies 22,23,26,[28][29][30][31][32] and the results regarding lifespan, cyclic fatigue resistance, shaping ability and cleaning efficiency were satisfactory.…”
Section: 24mentioning
confidence: 99%
“…27 The new single-use systems have been introduced to shape root canals with only one file: this technique simplification allows saving time and cost for endodontic treatment. 31 However, to shape root canals with only one file, the instrument will be subject to a great deal of stresses, both torsional and cyclic (bending) fatigue. This instrument is not used for further canals and not requires thermal sterilization in autoclave, so it will be not exposed to other stresses.…”
Section: -2428mentioning
confidence: 99%